Perceptions on the risk management of unused pharmaceuticals towards the creation of guidelines on handling and disposal - Antonio, Marianne Uy (Department of Pharmacy, College of Pharmacy, University of the Philippines Manila, 2013)
The increase usage of pharmaceuticals, its introduction and accumulation in the environment are growing environmental and health concerns and have been a topic of interests for several years now. Active Pharmaceutical Ingredients (APl) are developed and used because of their more or less specific biological activity. It is this very nature of medicines that they may also have an untoward effect on animals and microorganisms in and to the environment and an indirect effect to public health. The main objective of the study was to determine the perceptions on the risks and management of unused pharmaceuticals towards the creation of a guideline on its handling and disposal. The survey was completed by respondents from the pharmaceutical industries, pharmacies and residents of Valenzuela City. Three hundred thirty individuals from Valenzuela City completed the survey. Two hundred fifty of them had unused pharmaceuticals in their house. Most of them do not know how and where to dispose their unused pharmaceuticals. Respondents from pharmaceutical industries and pharmacies agreed that it is essential that the Philippine government should establish a guideline on handling and disposal of unused pharmaceuticals. Trash bin and sink are the favored method of disposal of unused pharmaceuticals by most of the respondents since there is no existing guideline on it: proper handling and safe disposal. All of them agreed that the Philippine government should initiate on educating and conducting a collection program or waste management strategies of unused pharmaceuticals.